Productivity and 15N isotope dilution of sugarcane inoculated with diazotrophic bacteria - Schultz, Nivaldo; Pereira, Willian; Reis, Veronica Massena; Urquiaga, Segundo Sacramento (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the productivity and 15N isotope dilution of two sugarcane varieties inoculated or not with diazotrophic bacteria. Two experiments were carried out in the Southeast and Northeast regions of Brazil, during three cropping seasons (2007/2008, 2008/2009 e 2009/2010): the first one on a clayey Acrisol, and the second one on a medium-textured Planosol. A randomized complete block design, with four replicates was used. The varieties RB867515 and RB72454 were tested with inoculation of diazotrophic bacteria (five strains combined in the inoculant for sugarcane) or fertilization with 120 kg ha-1 N, besides the control treatment without inoculation and nitrogen fertilization. Stalk yield and 15N isotope dilution of the flag-leaves were evaluated. The RB72454 variety showed greater response to the treatments during the plant-cane cycle and the second ratoon. 15N natural abundance in the flag-leaves decreases over the years, which suggests the increase of biological N fixation when N availability in soil reduces.